2017
DOI: 10.3846/16486897.2017.1281816
|View full text |Cite
|
Sign up to set email alerts
|

Watershed Road Network Analysis With an Emphasis on Fire Fighting Management

Abstract: The aim of this study is fire hazard zoning the Chehel-Chay watershed and analysis of road network in order to fire-fighting management. Using effective factors on fire occurrence, the fire hazard map of the study area produced by support vector machine algorithm and then was divided into four hazard classes. The road length and type were investigated in the each fire hazard classes. The results showed that most of occurred fires are located in the close distances of roads and forest areas. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The economic appraisal of an investment in a forest road is a complex process that should consider all costs and benefits, whether economic, social, environmental, or financial [58]. Costs and benefits in this context may comprise effects that can hardly be expressed in monetary values, such as strain damages along the forest boundary, influences on the ground water balance and sediment dispersion to streams [19], reduction of productive forest land [59], influences of the annual increment, increasing risk for windthrows along forest roads, provision of food for wildlife, better accessibility for recreation seekers and rescue services [24,30], obligation to ensure road safety, problems of acceptance by local communities [60], influences on biodiversity [13,26], and risk of forest disease [61]. This complexity may lead to prohibitively high transaction costs caused by stakeholder discussion, contact with authorities, required expert reports, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…The economic appraisal of an investment in a forest road is a complex process that should consider all costs and benefits, whether economic, social, environmental, or financial [58]. Costs and benefits in this context may comprise effects that can hardly be expressed in monetary values, such as strain damages along the forest boundary, influences on the ground water balance and sediment dispersion to streams [19], reduction of productive forest land [59], influences of the annual increment, increasing risk for windthrows along forest roads, provision of food for wildlife, better accessibility for recreation seekers and rescue services [24,30], obligation to ensure road safety, problems of acceptance by local communities [60], influences on biodiversity [13,26], and risk of forest disease [61]. This complexity may lead to prohibitively high transaction costs caused by stakeholder discussion, contact with authorities, required expert reports, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…where Ap is access percentage, while Aa and At are access and total area in hectares, respectively [14,31]. Road density measures the territorial ratio between the length L of the road segment and the unit area [13,16] (Equation (2)):…”
Section: Response Variablesmentioning
confidence: 99%
“…Many studies, including those by Elia et al [4], Mostafa et al [16] Hong et al [17], Bergonse et al [18], Sinha et al [19], and Zhang et al [20], have used road density and distance in wildfire mapping and modeling as independent variables. For example, Hong et al [17] found that the spatial distribution of wildfire susceptibility is correlated to landscape attributes that have been shaped by residential areas and road networks in Huichang County, China.…”
Section: Introductionmentioning
confidence: 99%
“…Forest roads are associated with spatial patterns of ignitions and fire perimeters, function as fuelbreaks and firebreaks, and can support safer and more effective wildfire management [1][2][3][4][5][6][7][8]. Addressing fire management needs with forest road network analysis and planning is therefore an important area of research, especially as climate and other factors contribute to increased fire activity in many areas around the globe [9][10][11][12][13]. Of interest here is how road networks support fire control operations, and how fire managers consider roads in pre-season assessment and planning.…”
Section: Introductionmentioning
confidence: 99%
“…Roads aid fire management by facilitating fire surveillance and prevention, supporting access and egress, providing safer locations for ground resources to engage fire, and enabling indirect tactics and burnout operations [11][12][13][14]. Factors influencing the utility of forest roads in control operations include topographic position (e.g., mid-slope, ridge top, or valley), adjacent vegetation, width and design standard (i.e., whether it can support heavy equipment and large vehicles), and maintenance condition.…”
Section: Introductionmentioning
confidence: 99%